Relationship of Body Mass Index with Dynamic Balance in Flatfoot Children Aged 9-12 Years - Putra, M. Daffa’ Alghifary Caesario; Abdurrachman, Abdurrachman (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2025)
Introduction: Flatfoot is a condition in which the inner arch of the foot (arcus medialis) is not formed when the child stands. Signs and symptoms of flatfoot such as abnormal walking patterns that cause fatigue and balance disorders. Low balance ability in children makes children prone to falls and experiences obstacles during activities. Purpose: The purpose of This study aims to determine the relationship between body mass index and dynamic balance in flatfoot children aged 9-12 years at SDIT Ulul Albab Pekalongan City. Research Method: This research design is quantitative with a cross-sectional approach. The sample was obtained by total sampling with a total of 107 respondents. Data analysis used univariate and bivariate analysis with a dynamic balance measurement tool in the form of a bridge with a validity level of 0.738 and reliability of 0.629. The normality test used Kolmogorov-smirnov and the correlation test used Spearman Rank. The results: The results of the Spearman rank correlation test obtained a p value of 0.115 (ρ>0.05) and an R value of -0.153, so there is no significant relationship between body mass index and dynamic balance in flatfoot children aged 9-12 years at SDIT Ulul Albab, Pekalongan City. Conclusion: There is no significant relationship between body mass index and dynamic balance in flatfoot children aged 9-12 years at SDIT Ulul Albab, Pekalongan City.